Oxygen-Tethered 1,6-Enynes and [4.1.0]-Bicyclic Ether Skeletons as Hedonic Materials for the Fragrance Industry - Laher, Romain; Gentilini, Emilie; Marin, Christophe; Michelet, Véronique (Synthesis, 2021)
The synthesis of original structures for the fragrance industry bearing bicyclic scaffolds is described. To the best of our knowledge, these structures are not found in the fragrance industry, neither from natural nor synthetic pathways. NHC–gold-type catalysts showed excellent activities leading to light bicyclic enol ethers. Several bicyclic adducts were prepared in good to excellent yields (18–99%). Evaluation of NHC–Au complexes allowed to reach a TOF of 300 h–1. The evaluation for the organoleptic properties of [4.1.0]-bicyclic ethers were compared with the unprecedented properties of the 1,6-enyne precursors. Evaluations of starting materials showed a great interest in these structures with various olfactory facets. In this study, we depicted the similarity and differences between starting ethers and their cycloisomerized bicyclic counterparts.
Keywords: gold catalysis; N-heterocyclic carbenes; fragrance; 1,6-enynes; bicyclic compounds